2008
DOI: 10.1111/j.1528-1167.2008.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Low glycemic index treatment: Implementation and new insights into efficacy

Abstract: SUMMARYDespite the substantial efficacy of the ketogenic diet (KD) in treating refractory epilepsy, use of the KD remains limited because of difficulties in implementation and tolerability. An effective alternative dietary approach is a low glycemic index treatment (LGIT), which liberalizes the extreme carbohydrate restriction of the KD but restricts the type of carbohydrate-containing foods to those that produce relatively small changes in blood glucose. Foods with a "glycemic index" of less than 50 produce l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 21 publications
(26 reference statements)
3
63
1
5
Order By: Relevance
“…All CHO foods' glycemic index are lower than 50. [15,16] This diet needs to be prescribed by a dietitian. Specific meal plans are not typically provided, but recommendations are made depending on food preferences and individual goals.…”
Section: Benefits and Limitations Of The Mctkdmentioning
confidence: 99%
See 1 more Smart Citation
“…All CHO foods' glycemic index are lower than 50. [15,16] This diet needs to be prescribed by a dietitian. Specific meal plans are not typically provided, but recommendations are made depending on food preferences and individual goals.…”
Section: Benefits and Limitations Of The Mctkdmentioning
confidence: 99%
“…Vitamins and minerals are supplemented to meet individual needs. [15,16] The balance of low glycemic CHO in combination with fat results in steady glucose levels. [15,16] The MAD does not need diet prescription.…”
Section: Benefits and Limitations Of The Mctkdmentioning
confidence: 99%
“…The LGIT prevents large postprandial increases in blood glucose, resulting in more stable circulating levels of glucose, and in early studies has been shown to provide seizure control in a broad range of patients ( 64,65 ). This diet also allows for a greater intake of carbohydrates ( ‫ف‬ 40-60 g/day), but this is restricted to those foods with a GI of <50 ( 64,65 ). Total caloric intake is determined based on patient's needs, with 20-30% of calories coming from protein and the remaining 60% from fats ( 64 ) ( Fig.…”
Section: The Lgitmentioning
confidence: 99%
“…The rationale for the LGIT was based on the clinical observation that the KD led to a sustained drop in blood glucose levels and on laboratory studies showing decreased seizure susceptibility in epileptic mice induced by CR (63). The LGIT prevents large postprandial increases in blood glucose, resulting in more stable circulating levels of glucose, and in early studies has been shown to provide seizure control in a broad range of patients ( 64,65 ). This diet also allows for a greater intake of carbohydrates ( ‫ف‬ 40-60 g/day), but this is restricted to those foods with a GI of <50 ( 64,65 ).…”
Section: The Lgitmentioning
confidence: 99%
See 1 more Smart Citation